Comparison of the Effectiveness of Schema Therapy and Narrative Therapy on the Psychological Well-being of Women Affected by Infidelity - Kashi Pazha, Anousheh; Sadeghian, Sahar; Vasheghani Farahani, Narjes; Haji Arab, Elham (Psychology of Woman Journal, 2024)
Objective: The present study aimed to compare the effectiveness of schema therapy and narrative therapy on the psychological well-being of women affected by infidelity. Methods and Materials: The research method was quasi-experimental with a pre-test, post-test, and control group design with a follow-up period. The statistical population of the present study included all women affected by infidelity who sought counseling services at centers located in District 1 of Tehran in 2024. A total of 45 individuals were purposefully selected and randomly assigned to two experimental groups and one control group. The instrument used in this research was the Psychological Well-Being Questionnaire (Ryff, 2002). The schema therapy intervention and White’s (2017) narrative therapy protocol were implemented in 12 group sessions, each lasting 120 minutes, conducted twice a week for the first and second experimental groups. Data were analyzed using mixed ANOVA. Findings: The results of the ANOVA indicated a significant difference in psychological well-being between the groups in the post-test and follow-up phases (P<0.05). The results showed that schema therapy was significantly more effective than narrative therapy in improving the psychological well-being of women affected by infidelity, and a significant difference was observed between the two treatments (P<0.05). Conclusion: It can be concluded that there is a significant difference between schema therapy and narrative therapy.